Effect of Antioxidant Supplementation on the Total Yield, Oxidative Stress Levels, and Multipotency of Bone Marrow-Derived Human Mesenchymal Stromal Cells - Alves, Hugo (Mary Ann Liebert, Inc., 2013)
Bone marrow-derived multipotent mesenchymal stromal cells (MSCs) are the most frequently investigated cell type for potential regenerative strategies because they are relatively easy to isolate and are able to differentiate into several mesenchymal lineages. Unfortunately, during ex vivo culture, MSCs present gradual loss of differentiation potential and reduced clinical efficacy. Reactive oxygen species (ROS) are associated with oxidative damage and accumulate during MSC expansion. Because ROS are believed to be involved in the loss of multipotency, we hypothesized that compounds with antioxidant activity have the capacity to scavenge ROS, prevent cellular damage, and rescue culture-induced loss of multipotency. In this manuscript, we show that antioxidant supplementation can partially rescue the loss of alkaline phosphatase expression induced by oxidizing agents and increases the yield of hMSCs, when supplemented to a fresh bone marrow aspirate. Concomitantly, oxidative DNA damage and ROS levels in hMSCs were reduced by antioxidants. We conclude that antioxidant supplementation during MSC expansion reduces the DNA damage load and increases the MSC yield.